New Metabolites From the Co-culture of Marine-Derived Actinomycete Streptomyces rochei MB037 and Fungus Rhinocladiella similis 35 - Yu, Meilin; Li, Yingxin; Banakar, Shivakumar P.; Liu, Lu; Shao, Changlun; Li, Zhiyong; Wang, Changyun (Frontiers in Microbiology, 2019)
Co-culture of different microbes simulating the natural state of microbial community may produce potentially new compounds because of nutrition or space competition. To mine its metabolic potential in depth, co-culture of Streptomyces rochei MB037 with a gorgonian-derived fungus Rhinocladiella similis 35 was carried out to stimulate the production of new metabolites in this study, using pure cultivation as control. Five metabolites were isolated successfully from co-culture broth, including two new fatty acids with rare nitrile group, borrelidins J and K (1 and 2), one chromone derivative as a new natural product, 7-methoxy-2,3-dimethylchromone-4-one (3), together with two known 18-membered macrolides, borrelidin (4) and borrelidin F (5). The structures of 1–3 were elucidated by using a combination of NMR and MS spectroscopy, ester hydrolysis, and optical rotation methods. Interestingly, 1 and 2 were obtained only in co-culture. Though 3 was gained from either co-culture or single culture, its production was increased significantly by co-culture. Compound 1 exhibited significant antibacterial activity against methicillin-resistant Staphylococcus aureus with a MIC value of 0.195 µg/mL.